International criminal responsibility for ISIS crimes - حسين الاء ناصر; مسلم نبراس ابراهيم (Journal of Legal Sciences, 2019)
In contest of the serious crimes committed by the gangs of the terrorist, it was necessary to shed light on how to prevent their impunity. Therefore, this research came to examine the composition of these gangs, their nature and source of funding, and then the nature of the crimes committed by them, and if their crimes fall in the International criminal law or only within the framework of the Iraqi criminal law, after that we were able to find out the nature of those crimes and thus the best mechanisms that represent the just punishment that these gangs deserve as a punishment for the crimes they committed against the unarmed civilians.